TEACHING READING STRATEGY FOR YOUNG LEARNERS - Maizarah Maizarah; Sri Erma Purwanti (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Nowadays English is a compulsary subject must be taught for students, because English is global language. English has some skills namely listening, speaking, reading and writing. One of the important skills is reading, because through reading students will have broad insight, so the habit of reading has to start with students in Elementary. Elementary students are English young learners that should be facilitated well in their learning reading by using good strategy. Teaching English for young learner is different with teaching English for adult learner. Young learners have different characteristics and learning preference. In teaching reading, English teachers should implement appropriate strategies and interesting to young learners which can be a stimulus to become active students and participate in teaching and learning process. Therefore, this article aimed to explain some reading strategies that can be applied by the teachers for young learners. The method employed is library research which has four steps to collecting the data namely note-taking, outlining, describing, and draw conclusion. The strategies that are described are Emergent Literacy, Mnemonic Strategy, Read aloud strategy, Decoding Strategy, and Language Experience Approach.